Toxicity and efficacy of intrathecal liposomal cytarabine in children with leukemia/lymphoma relapsing in the central nervous system: a retrospective multicenter study. Issue 3 (March 2015) - Parasole, Rosanna; Petruzziello, Fara; Messina, Chiara; Barisone, Elena; Pession, Andrea; Locatelli, Franco; Micalizzi, Concetta; Cesaro, Simone; Testi, Anna Maria; De Matteo, Antonia; Varotto, Stefania; Berger, Massimo; et al.
Abstract: The toxicity and efficacy of intrathecal liposomal cytarabine (LC) were evaluated in children with central nervous system (CNS) relapsed/refractory acute leukemia/lymphoma. Thirty patients (male:female ratio 21:9; median age 9.4 years) with CNS relapsed/resistant disease were treated with intrathecal LC at dosages adjusted for age. Twenty-seven (90%) patients simultaneously received systemic chemotherapy, including concurrent high-dose cytarabine or methotrexate in 21 (70%) cases. Of 28 patients evaluable for response, 25 patients (89%) achieved CNS complete remission and three (11%) partial remission. The median number of intrathecal LC administrations per patient was 4. The cerebrospinal fluid was cleared after a median of 3 intrathecal LC administrations. Neurological toxicity ≥ grade 3 occurred in four (13%) patients. No permanent sequelae were observed. The median overall survival was 20.9 months and the 5-year probability of survival was 46%. These encouraging data suggest that intrathecal LC is well tolerated and effective in children with relapsed/refractory CNS leukemia/lymphoma.